Comparative Efficiency Analysis in Recuperative Electrical Drives: A Study of LVDC vs. LVAC-Protection Components and Grid Integration - Gutwald, Benjamin; Korneev, Aleksandr; Römer, Patrick; Barth, Martin; Reichenstein, Tobias; Franke, Jörg (2024 1st International Conference on Production Technologies and Systems for E-Mobility (EPTS), 2024)
Based on a full factorial metrological analysis, part 1 ("power supply") of the publication series demonstrates the great energy-saving potential for the operation of electric drives on the direct current (DC) grid. In the analysis, the energy requirement of a drive system with a DC supply could be reduced between 12 and 25 % compared to an alternating current (AC) supply. In order to realize the promising supply concept via a DC grid, a safe switching and protection concept is required to integrate the drive. Due to a lack of experience with powerful industrial DC grids, most planners and installers do not have the knowledge to plan and commission such electrical systems in accordance with regulations. In addition, the respective switching and protective devices influence the efficiency of the overall system. This publication offers decision-making aids for grid integration to enable the practical feasibility of the concept outlined in Part 1. It covers the selection and design of the protection concept. Specifically, two concepts for switching and protection of drive controllers on the DC-side, with different costs and safety standards, are proposed and compared to an established protection concept for AC supply. The proposals are based on relevant international standardization. Part 1 of this publication only considered the drive controller's electrical power consumption, but this section also measured and compared the load-dependent losses of each component of the associated protection scheme. Depending on the system voltage, power range and planning variant, the measured losses in AC operation are twice as high. The loss characteristics are made up of the ohmic losses with a quadratic gradient with the current flow and an offset due to the constant power requirement of the control circuit. Reactive power only occurs in the AC system and significantly increases the losses of the protective devices and the transmission system. Based on several test setups, this publication provides a holistic efficiency comparison for the DC-based energy supply of drive systems. It provides a design and decision-making aid for system planners, installers and commissioning engineers as well as investment management and thus makes a significant contribution to the roll-out of environmentally friendly DC grids.
CRIS-Team Scopus Importer:2024-08-02
Keywords: direct current; Electrical drives; energy efficiency; frequency converter; protection; recuperation; safety